Promotion Development Through Social Media for OTOP Branding: A Community-Based Approach - Narimawati, Umi; Siti Kurnia Rahayu; Watcharapong Ratchakulwongwarit; Witchu Aromdee; Sarip hidayat; Muhammad Akhdiyatul Aein; Rudi Saputra (International Journal of Community Service (IJCS), 2025)
The international community service program entitled Promotion Development Through Social Media for OTOP Branding: A Community-Based Approach was conducted on August 26, 2025, at the Bang Prong Subdistrict Administrative Organization Office, Samut Prakan, Thailand. The main objective of this initiative was to enhance the capacity of OTOP entrepreneurs in understanding branding concepts and utilizing social media as a promotional tool. The methods included a product exhibition, production process demonstrations, and interactive workshops that emphasized content creation, hashtag strategies, and business account management. The results revealed significant improvements in participants’ comprehension of branding, their skills in generating promotional content, and their confidence in conducting online promotion. Furthermore, the program demonstrated that community-based approaches foster participatory learning and effective peer-to-peer exchange. The cross-border collaboration between Universitas Komputer Indonesia and Thai Global Business Administration Technological College also enriched the program by ensuring international knowledge transfer adapted to local contexts. In conclusion, the initiative highlights the importance of integrating modern branding practices with local wisdom to strengthen OTOP competitiveness in the digital era and to support sustainable community-based entrepreneurship.